Microbial diversity and flavor of Chinese rice wine (Huangjiu): an overview of current research and future prospects. (December 2021) - Chen, Gui-Mei; Huang, Zi-Rui; Wu, Li; Wu, Qi; Guo, Wei-Ling; Zhao, Wen-Hong; Liu, Bin; Zhang, Wen; Rao, Ping-Fan; Lv, Xu-Cong; Ni, Li; Sun, Jin-Yuan; et al.
Abstract : Chinese rice wine ( Huangjiu ), a typical representative of traditional fermented foods in China, is distinguished for its unique flavor. Microorganisms play the most important role in the formation of the unique flavor of Huangjiu . The complex flavor components in Huangjiu are closely related to the metabolism of various microorganisms during the traditional brewing. Therefore, understanding the influence of microbiota on the formation of flavor components in Huangjiu is conducive to the production of Huangjiu with high-quality flavor. In recent years, many scholars have conducted a large number of studies on the microbial community and flavor metabolites during the traditional brewing process of Huangjiu, with the help of high-throughput sequencing (HTS) and mass spectrometry-based metabolomics. This review mainly summarized the current study progress of the microbial diversity of fermentation starters ( Qu ) and brewing process of Huangjiu, and explored the potential relationship between the microbial community and the characteristic flavor formation of Huangjiu . Through the comparative analysis of literatures, we found that Huangjiu has strong regional characteristics due to the differences in raw materials, Qu and traditional brewing techniques. Dynamics of microbial composition during the traditional brewing of Huangjiu in different regions of China are quite different, making Huangjiu in each region have their own flavor characteristics. Therefore, revealing the relationship between brewing microorganisms and flavor characteristics of Huangjiu is helpful to the directional regulation of flavor quality. According to the current research status, it is proposed that in the future, emerging technologies such as multi-omics, artificial intelligence, and machine learning should be applied to further improve the accuracy of the analysis of microbial flora and flavor components in Huangjiu, so as to accurately reveal the relationship between the microbial community and the formation of characteristic flavor of Huangjiu . Afterwards, high-throughput screening of excellent functional strains from the traditional brewing system should be applied to the industrial production of Huangjiu, so as to improve the overall flavor quality and commercial value.